(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2020)
The present research investigated multi-zone single-cylinder four-stroke direct-injection model. The model simulates closed cycle processes and describes the combustion behavior by employing thermodynamic equations of a penetration spray theories. The model has been coded on the base of the programming tools of Matlab software. In this simulation model, the combustion events is divided into five zones, in order to determine the amount of fuel, access air, and amount of products in each zone. The simulation model, produced in this work, provides a more accurate framework for zero dimensional model by introducing physical zones within the model that correspond to the combustion structures in the engine. Comparison the results of the simulation model with other methods in the published researches shows that the behavior of engine parameters with theoretical and experimental earlier works has a good agreement. From the simulation model results can be concluded that, there is a change in the limits of the combustion zones with changing engine speed, amount of injected fuel, intake air pressure, and temperature, especially in the rich premixed burn zone.